Certain Classes of Univalent Functions With Negative Coefficients Defined By General Linear Operator - Mazin Sh.Mahmoud; Abdul Rahman S.Juma; Raheam A. Mansor Al-Saphory (Tikrit Journal of Pure Science, 2019)
In this study, a subclass of an univalent function with negative coefficients which is defined by anew general Linear operator have been introduced. The sharp results for coefficients estimators, distortion and closure bounds, Hadamard product, and Neighborhood, and this paper deals with the utilizing of many of the results for classical hypergeometric function, where there can be generalized to m-hypergeometric functions.